PERAN BUDAYA SEKOLAH DALAM PENINGKATAN KINERJA GURU - Christina Oktaviani (Manajer Pendididikan, 2015)
The aim of this research is to know how is the role of a school’s culture in increasing the performance of teachers in Sint Carolus senior high school Bengkulu. The data collected techniques used in this research are observation, interview, and documentation. The subjects are the principal, vice principal, teachers, administration staff, janitor, and security. The result of this research showed that school’s culture: behavioral patterns, the followed norms, the dominant values, the philosophy, the regulation, and the atmosphere of the school have an important roles in increasing the performance of teachers.Key word: school culture, teacher performance